Iraq : 2017 Article IV Consultation and Second Review under the Three-Year Stand-by Arrangement-and Requests for Waivers of Nonobservance and Applicability of Performance Criteria, and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights a double shock facing Iraq as a result of the conflict with the Islamic State and the plunge in oil prices. In 2016, real GDP increased by 11 percent owing to a 25 percent increase in oil production, which was little affected by the conflict with the Islamic State. Falling oil prices have driven the decline in Iraq's international reserves from USD 54 billion at the end of 2015 to USD 45 billion at the end of 2016. Medium-term growth prospects are positive. Growth will be driven by the projected moderate increase in oil production and the rebound in non-oil growth supported by the expected improvement in security and implementation of structural reform.